PENGARUH INVENTORY INTENSITY,PROFITABILITY,LIQUIDITY DAN CAPITAL INTENSITY TERHADAP AGRESITIVITAS PAJAK - Riski Puspita Anggraini; Heni Agustina (Jurnal Ilmiah Raflesia Akuntansi, 2022)
The act of tax aggressiveness is one that can worsen the company's image. This is because the company's profits increase and the taxes paid are high, so the company carries out tax aggressiveness so that the profits obtained are maximized. Inventory intensity, profitability, liquidity, and capital intensity can be used to minimize corporate tax aggressiveness. This objective was conducted to determine the effect of inventory intensity, profitability, liquidity, and capital intensity on tax aggressiveness. The research was conducted on property and real estate companies listed on the Indonesia Stock Exchange for the period 2013-2020. The sampling method used was purposive sampling. The data analysis used is multiple linear analysis. The results of the study show that there is no effect between inventory intensity and tax aggressiveness. Profitability and liquidity have a negative and significant effect on tax aggressiveness, while capital intensity has a positive and significant effect on tax aggressiveness.